ENTREPRENEURSHIP AND SMALL BUSINESS PERFORMANCE DURING COVID-19: THE MEDIATING EFFECT OF DYNAMIC CAPABILITIES - Matejun, Marek; Ratajczak, Marcin (Acta Scientiarum Polonorum. Oeconomia, 2023)
Aim: The aim of the study is to explore the role of dynamic capabilities as a factor mediating the impact of owner-manager entrepreneurial characteristics on small business performance during the COVID-19 pandemic. Based on the literature review, 3 hypotheses were formulated, and a research model was built. Methods: To achieve the aim of the study, survey research was conducted on a random sample of 564 micro-, small-, and medium-sized enterprises from Poland and the Czech Republic. Results: The results indicate that the entrepreneurial characteristics of owner-managers have a significant and positive impact on small business performance during the COVID-19 pandemic. This impact is also mediated by the development of dynamic capabilities of the surveyed SMEs. Within these characteristics, strategic thinking expressed in a coherent vision of business development and a strong motivation to achieve business success played a special role. Also important was courage and effectiveness in dealing with challenges and unforeseen market situations, as well as open-mindedness and creativity in developing and implementing new projects and ways of doing things. The results also provide in-depth insights for understanding the formation of a resource-based approach in small businesses. It significantly determines the strategic success, internationalization, and innovation of this category of businesses in dynamic and uncertain business environments. Conclusions: The conclusions from this study enrich the theory of entrepreneurship by explaining the complex role of entrepreneurs in small business resilience under crisis situations. They also provide important conclusions for understanding the development of the resource approach of SME sector companies in dynamic and uncertain business environments, as well as for the development of prospective entrepreneurial education programs.